NOBCChE News, Volume 20, Number 1 (National Organization for Black Chemists and Chemical Engineers, 1999)
Winter 1999 issue of NOBCChE News.
Keywords: National Organization for Black Chemists and Chemical Engineers; Chemists; Chemical engineers; African American chemists; African American engineers; Newsletters; Periodicals; Scientists, Black; African American scientists